Alkaloid profile of endophytic Diaporthe spp. from Cinchona calisaya - Radiastuti, Nani; Rahayu, Gayuh; Okane, Izumi; Hidayat, Iman; Achmadi, Suminar S. (Research Institute for Tea and Cinchona, 2015)
Endophytic fungi have been known as potential source of bioactive compound, similar to their host.Â This study was conducted to identify endophytic Diaporthe spp. isolated from Cinchona calisaya and to explore their potential in producing alkaloids, particularly quinine. A total of 39 strains of Diaporthe spp. were identified using ITS1-5.8S-ITS2 and EF1-Î± gene. Seventeen strains have species name and they represent eight species of Diaporthe i.e. D. cynaroidis, D. endophytica, D. ganjae, D. gardeniae, D. litchicola, D. phaseolorum, D. pseudomangiferae, and D. rhoina. The reÂmaining 22 strains represents 15 groups of unidentified Diaporthe sp. High performance liquid chromatography analyses of chloroform extract of 21-days old static cultures of all fungi in potato dextrose broth showed that these strains produce totally 82 different alkaloids. Each strain producedabout 2-38 different alkaloids. Sixteen out of 39 strains (41%), i.e. one strain each of D. endophytica, D. garÂdeniae, Â D. phaseolorum, and Â D. pseudoÂmangiferae, 2 strains of D. litchicola, and 10 strains of unidentified Diaporthe were able to produce quinine. The quinine concentration ranges from 1.1 mg/l to 155.2 mg/l. By using Jaccardâs similarity index 0.44 as the cutting score, UPGMA analyses of alkaloid profile of these strains shows that these strains forms 23 clusters. Alkaloid profile clustering does not support the phylogenetic grouping. This indicates that the alkaloid profile is strain dependent. Some potential strains should be further investigated for optimization of their quinine production.